2018
DOI: 10.1111/evo.13589
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise evolution of floral pigmentation predicted by biochemical pathway structure

Abstract: Developmental pathways play a major role in influencing the distribution of naturally occurring phenotypes. For example, pathway structure and regulation could make some phenotypes inaccessible or restrict the routes through which phenotypes evolve. In this study, we examine floral anthocyanin pigments across the Solanaceae family and test whether patterns of phenotypic variation are consistent with predicted constraints based on the structure of the flavonoid biosynthetic pathway. We find that anthocyanin evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 97 publications
0
13
0
Order By: Relevance
“…In addition to deoxyanthocyanidins, several hydroxyanthocyanidins (pelargonidin, cyanidins, delphinidin) were also found in various combinations across the Gesnerioideae (Figure 3 and Supplementary Figure S1). A previous study on Solanaceae reported that, even though the species of this family were able to produce all three main groups of anthocyanins, they often produce only one type of anthocyanin or a mix of two anthocyanins with consecutive hydroxylation levels (e.g., pelargonidin-cyanidin or cyanidinmalvidin), and none of the studied species produced all three pigment types (Ng et al, 2018). It has been proposed that the anthocyanin composition is constrained by the stepwise structure of the biosynthetic pathway that leads to the successive production of the red mono-hydroxylated pelargonidin, purple di-hydroxylated cyanidin, and the blue tri-hydroxylated delphinidin pigments (des Marais and Rausher, 2008;Ng et al, 2018).…”
Section: The Alternative Branches Of the Anthocyanin Pathway In The Gmentioning
confidence: 89%
See 1 more Smart Citation
“…In addition to deoxyanthocyanidins, several hydroxyanthocyanidins (pelargonidin, cyanidins, delphinidin) were also found in various combinations across the Gesnerioideae (Figure 3 and Supplementary Figure S1). A previous study on Solanaceae reported that, even though the species of this family were able to produce all three main groups of anthocyanins, they often produce only one type of anthocyanin or a mix of two anthocyanins with consecutive hydroxylation levels (e.g., pelargonidin-cyanidin or cyanidinmalvidin), and none of the studied species produced all three pigment types (Ng et al, 2018). It has been proposed that the anthocyanin composition is constrained by the stepwise structure of the biosynthetic pathway that leads to the successive production of the red mono-hydroxylated pelargonidin, purple di-hydroxylated cyanidin, and the blue tri-hydroxylated delphinidin pigments (des Marais and Rausher, 2008;Ng et al, 2018).…”
Section: The Alternative Branches Of the Anthocyanin Pathway In The Gmentioning
confidence: 89%
“…On the other hand, bird-pollinated flowers frequently have a distinctive orange/red color, which is better detected by birds than by bees especially against a green vegetation background (Lunau et al, 2011;Shrestha et al, 2013;Burd et al, 2014;Bergamo et al, 2016). Despite the importance of color signaling in plantpollinator interactions, the biochemical basis of color shifts has been investigated in a limited number of studies (Hoballah et al, 2007;Sobel and Streisfeld, 2013;Ng and Smith, 2016), and our understanding of how pigment biosynthesis pathways shaped the evolution of floral color is still limited (Cronk and Ojeda, 2008;Rausher, 2008;Ng et al, 2018;Wheeler and Smith, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Organizing the simulations around this stepwise sequence of transitions allowed us to circumvent issues that arise from epistasis in the pathway model, wherein different starting states can result in differences between trajectories that are difficult to interpret (Ng et al. 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Considering the structure of the flavonoid pathway, these represent stepwise shifts from three to two to one hydroxyl groups on the flavonoid backbone, and phylogenetic modeling shows that these stepwise transitions are the primary mode of evolutionary change (Ng et al. 2018). Transitions from blue to purple and purple to red have occurred in parallel in many clades and have been studied at the genetic level in several species pairs (Wessinger and Rausher 2012).…”
Section: Figurementioning
confidence: 99%
“…We evolved this mean 90% delphinidin state (hereafter referred to as simply the delphinidin state) to a 90% cyanidin state (corresponding to purple; hereafter referred to as simply the cyanidin state) and nally repeated the procedure to simulate the transition from cyanidin to 90% pelargonidin (corresponding to red; hereafter referred to as the pelargonidin state). Organizing the simulations around this stepwise sequence of transitions allowed us to circumvent issues that arise from epistasis in the pathway model, wherein dierent starting states can result in dierences between trajectories that are dicult to interpret (Ng et al 2018).…”
Section: Design Scheme For the Evolutionary Simulationsmentioning
confidence: 99%